LOSS AND GRIEF AS EXPRESSED THROUGH FLOWERS IN ENGLISH LITERATURE (BASED ON SHAKESPEARE’S WORKS) - Khazratkulova, Feruza (Foreign Languages ​​in Uzbekistan (JOURNALFLEDU.COM), 2025)
This article undertakes a comprehensive linguistic and poetic analysis of the symbolic and cultural–functional significance of floral and botanical imagery in the artistic representation of death and loss within English literature. The focus of the research is William Shakespeare’s renowned tragedies–Hamlet, Othello, and Romeo and Juliet–in which flowers and plants acquire a profound symbolic role, serving as a poetic medium to reveal psychological anguish, grief, memory, and the transient nature of human life. By employing comparative and analytical methods, the study systematically examines the poetic function of floral symbols, their cultural and intertextual foundations, and their aesthetic value in dramatic composition. Particular attention is given to Ophelia’s descent into madness and her symbolic distribution of imaginary flowers in Hamlet, Desdemona’s mournful “Willow Song” in Othello, and the interlacing of nuptial and funerary imagery in Romeo and Juliet, where floral motifs underscore themes of tragedy and destiny. The article demonstrates that Shakespeare’s use of nature-related symbols extends beyond decorative imagery, functioning as a linguistic and cultural code through which psychological depth and philosophical reflections on life and death are expressed. The findings contribute to a deeper understanding of Shakespearean poetics, emphasizing the interplay between symbolic language, cultural tradition, and narrative structure. Furthermore, this research lays a theoretical foundation for subsequent scholarly inquiries into the role of symbolic imagery in English literature, providing a methodological framework for comparative studies of floral motifs in various cultural contexts. Thus, the article represents both a detailed textual interpretation and a broader contribution to literary semiotics and cultural linguistics.
Keywords: Shakespearean poetics; floral and botanical symbolism; tragic dramaturgy; linguopoetic analysis; semiotics and symbol systems; Elizabethan cultural context; ethnobotany; contextual interpretation; comparative analysis methodology; themes of death and mourning